A Multilevel Analysis of Factors Influencing Bullying Victimization at School among Indonesian Students with Binary Outcome (International Journal of Scientific Research and Management (IJSRM), 2024)
Bullying is an aggressive act toward someone who cannot defend themselves. Students who experience bullying victimization are treated badly by their friends, such as by being teased, ostracized, or kicked. Therefore, this study aims to determine the influencing factors of students being bullied among Indonesian students. The data used is secondary data from the 2022 Program for International Student Assessment (PISA) for Indonesia, with a sample comprised of 11,479 students from 403 schools. Data analysis uses a multilevel model with a binary response because the data is hierarchically structured, and the response variable is binary. The results show that male students, who have missed school, are late for school, repeat a grade, have low grade levels, low teacher support, low discipline, rural schools, and those with small class sizes will have a higher chance of experiencing bullying victimization more often. Overall, this study helps explain the influencing factors of students being bullied so that these factors can be given more attention to improving school policies.